A Study of the fole of Flavonoids and phenolic compounds in Indonesian herbs as sources of modern natural medicines - fhadillah, davyana allya (Maliki Interdisciplinary Journal, 2026)
Flavonoids and phenolic compounds are a group of secondary metabolites found abundantly in Indonesian herbal plants and possess various important pharmacological activities, including antioxidant, anti-inflammatory, immunodilatory, and antihypertensive properties. Phenolic compounds have been widely used, particularly in the health and food industries. Phenolics act as hydrogen donors, free radical scavengers, lipid oxidation inhibitors, and modulators of cellular signaling pathways. Significant bioactivity is observed in various herbal extracts, such as Kaemferiae galanga, date palm seeds, gandaria, and starfruit, which contain flavonoids and phenolics with high pharmacological potential. Currently, there is increasing interest in the therapeutic potential of medicinal plants, possibly related to their phenolic groups, particularly flavonoids. Flavonoids have been consumed by humans for a long time. Flavonoids have broad biological capabilities in maintaining human health and helping reduce the risk of various diseases. These compounds exhibit the ability to reduce oxidative stress, inhibit angiotensin-converting enzyme activity, increase vascular endothelial relaxation, and regulate cell signaling and gene expression. Oxidative stress is a condition that occurs due to an imbalance between free radical production and the body’s antioxidant defense system. Consuming herbal supplements is currently a trend for maintaining health (preventive) because it is considered more practical and has no side effects. Therefore, these compounds have great potential to be developed as the basis for developing safe and effective modern herbal medicines.